2012
DOI: 10.1111/j.1755-3768.2012.02576.x
|View full text |Cite
|
Sign up to set email alerts
|

Computer assisted evaluation of retinal vessels tortuosity in Fabry disease

Abstract: . Purpose:  Fabry Disease (FD) is a rare X‐linked metabolic disorder characterized by diffuse deposition of sphingolipids in many tissues. Retinal vessel tortuosity is a common ocular manifestation in FD and may represent a useful marker for the disease. Unfortunately its clinical evaluation is poorly reproducibile and alternative means of evaluation may be of interest. We tested a new semi‐automatic software measuring retinal vessel tortuosity from eye fundus digital images in a group of FD patients. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 29 publications
3
35
0
Order By: Relevance
“…Posterior lens cataract has previously been described as a specific feature in FD 37. This type of cataract has been reported in a few studies only with a prevalence up to 53% of men with FD 12 24 30 35…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Posterior lens cataract has previously been described as a specific feature in FD 37. This type of cataract has been reported in a few studies only with a prevalence up to 53% of men with FD 12 24 30 35…”
Section: Discussionmentioning
confidence: 83%
“…One of the registry studies reported a CV prevalence of 75% (men 73%, women 77%),30 while the second reported that in 11% of men and 12% of women CV was the presenting symptom 34. The high-risk group screening studies revealed that CV was absent in all adult individuals (n=29, 12 men) who were identified with a GLA variant 32 33…”
Section: Resultsmentioning
confidence: 99%
“…It is the quantification of these tortuosity metrics which provides a new way to describe tumors using ultrasound imaging (Gessner et al 2012). Tortuosity associated with malignancy has been used previously with other imaging modalities such as magnetic resonance angiography (MRA), photoacoustic tomography, microscopy, and computed tomography (CT) (Jain 2003; Bullitt et al 2004; Bullitt et al 2005b; Bullitt et al 2006; Badea et al 2008; Laufer et al 2012; Sodi et al 2013). However, ultrasound applications of tortuosity metrics have primarily been limited to quantification of skeletonizations from intensity thresholding of Doppler ultrasound images (Huang et al 2008; Molinari et al 2010; Chang et al 2012; Molinari et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Tortuosity is also applied in clinical settings to differentiate between benign and malignant tumours [14], [15] or to characterize retinal vascular changes [16]. The most common metric of vascular tortuosity is the “distance metric”, which provides a ratio of the actual vessel path length to the linear distance between its endpoints [17], [18].…”
Section: Introductionmentioning
confidence: 99%